Paul’s Christomorphic Wisdom in 1 Corinthians: Eschatological Telic Revelation according to a Pastoral Hermeneutic of Wisdom - Boerger, Jonathan D. (Journal of theological interpretation, 2024)
This article compares recent disparate hermeneutical proposals in order to draw out essential elements of a Christian hermeneutic of wisdom, which involves the tension of the gift and call of the gospel and recognizes Christ as the essential point of orientation. This approach is applied to 1 Corinthians, (re)reading chs. 1-4 in light of ch. 13 and thereby demonstrating that Paul’s view of wisdom is a qualitative, holistic integration of devotions, convictions, and actions. For Paul, the gospel of Christ is not just Christocentric in content and focus, but also Christomorphic in form and effect. On this basis, this article argues that in 1 Corinthians Paul portrays true wisdom as the Christomorphic edification of the church toward the eschatological telic revelation of the wisdom of Jesus Christ, which involves an essential tension between what is known and what is unknown yet will be revealed in Christ.